2022
DOI: 10.3389/fmicb.2022.925209
|View full text |Cite
|
Sign up to set email alerts
|

The attenuated Mycoplasma bovis strain promotes apoptosis of bovine macrophages by upregulation of CHOP expression

Abstract: Mycoplasma bovis (M. bovis) is one of the major pathogens in the bovine respiratory disease complex, which includes pneumonia, mastitis, and arthritis and causes a great economic loss in the cattle industry. In China, a live-attenuated vaccine strain M. bovis P150 was obtained by a continuous culture of the wild-type strain M. bovis HB0801 (P1) in vitro for 150 passages. Using the infected bovine macrophage cell line BoMac, this work attempted to investigate the mechanism of P150 attenuation and protective imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…There is currently no consensus on the correlation between M. bovis infection and host apoptosis. While some studies suggested that M. bovis infection triggers host cell apoptosis, others indicated that M. bovis does not modulate or inhibit apoptosis [40,[58][59][60]. We surmise that this discrepancy may be strain-dependent, as demonstrated by Maina et al that the bovine isolate strain Mb1 inhibits host macrophage apoptosis while the bison isolate strain Mb304 does not [24].…”
Section: Plos Pathogensmentioning
confidence: 70%
See 1 more Smart Citation
“…There is currently no consensus on the correlation between M. bovis infection and host apoptosis. While some studies suggested that M. bovis infection triggers host cell apoptosis, others indicated that M. bovis does not modulate or inhibit apoptosis [40,[58][59][60]. We surmise that this discrepancy may be strain-dependent, as demonstrated by Maina et al that the bovine isolate strain Mb1 inhibits host macrophage apoptosis while the bison isolate strain Mb304 does not [24].…”
Section: Plos Pathogensmentioning
confidence: 70%
“…bovis infection triggers host cell apoptosis, others indicated that M . bovis does not modulate or inhibit apoptosis [ 40 , 58 60 ]. We surmise that this discrepancy may be strain-dependent, as demonstrated by Maina et al .…”
Section: Discussionmentioning
confidence: 99%